Roles of osteocytes in phosphate metabolism - Michigami, Toshimi (Frontiers in Endocrinology, 2022)
Osteocytes are dendritic cells in the mineralized bone matrix that descend from osteoblasts. They play critical roles in controlling bone mass through the production of sclerostin, an inhibitor of bone formation, and receptor activator of nuclear factor  B ligand, an inducer of osteoblastic bone resorption. Osteocytes also govern phosphate homeostasis through the production of fibroblast growth factor 23 (FGF23), which lowers serum phosphate levels by increasing renal phosphate excretion and reducing the synthesis of 1,25-dihydroxyvitamin D (1,25(OH)2D), an active metabolite of vitamin D. The production of FGF23 in osteocytes is regulated by various local and systemic factors. Phosphate-regulating gene homologous to endopeptidase on X chromosome (PHEX), dentin matrix protein 1 (DMP1), and family with sequence similarity 20, member C function as local negative regulators of FGF23 production in osteocytes, and their inactivation causes the overproduction of FGF23 and hypophosphatemia. Sclerostin has been suggested to regulate the production of FGF23, which may link the two functions of osteocytes, namely, the control of bone mass and regulation of phosphate homeostasis. Systemic regulators of FGF23 production include 1,25(OH)2D, phosphate, parathyroid hormone, insulin, iron, and inflammation. Therefore, the regulation of FGF23 in osteocytes is complex and multifactorial. Recent mouse studies have suggested that decreases in serum phosphate levels from youth to adulthood are caused by growth-related increases in FGF23 production by osteocytes, which are associated with the down-regulation of Phex and Dmp1.